Investigation of the Optimal Percentage from Polyvinyl Alcohol on Flexural Strength of Cement Mortar Composite - A. Abbas, Waleed; N. Korkess, Iqbal; Jasim H., Mahdi (International Journal of Engineering and Technology, 2018)
Polyvinyl alcohol solution(PVA) proveded potential enhancement of the properties of cement mortar composite. This work investigated the effect of (w/c) and polymer-cement ratios (p/c) on the flexural strength of type I Portland cement mortar. A sand-cement ratio (s/c) of 1.25 and 0.5 by mass was used, and PVA powder was dispersed in water at (0.7%, 1%, 2%, and 3%) by weight of cement. The p/c solution was adjusted at five different values of 0.008, 0.012, 0.016, 0.020 and 30% covering relatively low and high values. Two types of curing were used; wet and dry curing. The study results demonstrated that flexural strength and significant water absorption properties of Portland cement mortar, as well as workability can be basically enhanced by the addition of PVA. Composite was prepared with optimum (p/c) 1.6% at concentration of 1% by mass under dry curing. The highest flexural strength was above twice the flexural strength of unmodified mortar. Also modified mortar samples illustrated that increasing of (p/c) causes reducing water absorption due to the packing effect caused by PVA, while mortar prepared at 0.1 and 0.3 w/c and (p/c) respectively, exhibited an increase in flexural strength which was more than the strength of unmodified mortar.Â Â